CityCenter, Las Vegas: 'De-Theming' in the Neoliberal City - Kurt Kraler (Media Theory, 2018)
The opening of CityCenter, Las Vegas in 2009 marked the single largest privately funded?development in American history. The sprawling resort campus signalled a departure from all-encompassing themes of kitsch that had long defined the Las Vegas Strip, obfuscating the threshold between public and private. It is indicative of the broader push for deregulation and monopolization that are characteristic of neoliberal processes. This raises pertinent questions around the implications of the apparent ‘de-theming’ of these leisure environments and the wider normalization of neoliberal principles in architecture and urbanism. The seminal Learning from Las Vegas identified the merging of sign and building alongside the widespread adoption of neoliberal ideology, where the roadside sign advanced from “decorated shed” to “duck” to atmospheres and, eventually, urbanism. Employing Gilles Deleuze and Félix Guattari’s concepts of “de-territorialization” and “re-territorialization,” this process of de-theming can be theorized as the reconfiguration of leisure as the totalizing image of gentrification and urban renewal.